Efficacy and safety of subliminal transscleral cyclophotocoagulation in uncontrolled glaucoma - Ferzana Mohammed; Sandhya Somasundaran; Suma Unnikrishnan; P T Jyothi (Indian Journal of Ophthalmology, 2022)
Purpose: To determine the efficacy of subliminal cyclophotocoagulation in reducing intraocular pressure (IOP) and to assess the safety profile of the procedure. Methods: We reviewed the charts of all patients who underwent subliminal cyclophotocoagulation between August 2019 and August 2020. The IOP, number of antiglaucoma medications, and visual acuity were compared at baseline and at 6 months. The post-laser complications were noted. Paired t-test, Wilcoxon rank-sum test, and McNemar test were used for analysis. Results: This study included 40 eyes of 40 patients. The most frequent diagnosis was neovascular glaucoma (55%), followed by primary open-angle glaucoma (17.5%). The mean IOP reduced from 32 to 21 mmHg (mean IOP reduction: 32%, 95% confidence interval [CI]: 27%–37%, P < 0.001). Mean number of antiglaucoma medications declined from 3.2 to 1.9 (P < 0.001). Use of oral acetazolamide decreased from 62% to 5% (P < 0.001). The success rate of the procedure at 6 months was 55%. One patient had unexplained visual acuity decline after the procedure. Conclusion: Subliminal sub-cyclophotocoagulation is effective in treating refractory glaucoma in the Indian population. It decreases the medication burden. However, subliminal lasers can also cause vision-threatening complications such as hypotony, uveitis, and optic nerve hypoperfusion. So, clinicians should be cautious when using sub-cyclophotocoagulation in patients with good vision.